2015 15th International Conference on Application of Concurrency to System Design 2015
DOI: 10.1109/acsd.2015.17
|View full text |Cite
|
Sign up to set email alerts
|

A Heuristic Algorithm for Deriving Compact Models of Processor Instruction Sets

Abstract: Finding a compact formal representation of a processor instruction set is important for easier comprehension by the designer, as well as for synthesis of an efficient hardware implementation of the processor's microcontroller.We present a new heuristic algorithm for deriving compact models of processor instruction sets. The algorithm is based on finding similarities between pairs of instructions and assigning similar opcodes (using a Hamming distance metric) to similar instructions (using a newly introduced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Our experiments have shown that only heuristic CPOG synthesis [22] can cope with event logs of realistic sizes. Other, more sophisticated encoding methods are not scalable enough.…”
Section: Details Of Current Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…Our experiments have shown that only heuristic CPOG synthesis [22] can cope with event logs of realistic sizes. Other, more sophisticated encoding methods are not scalable enough.…”
Section: Details Of Current Implementationmentioning
confidence: 99%
“…A more sophisticated approach, which produces CPOGs with more complex conditions has been proposed in [21], however, it has poor scalability and cannot be applied to large process mining instances. The most scalable approach to date, as confirmed by the experiments in §7.3, has been developed in [22] and is based on simulated annealing. All encoding methods are supported by open-source modelling framework Workcraft [7], which we used in our experiments.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…7), the function heuristicEncoding handles the output of the previous function enc and advances to enc best through a sequence of swap moves that inspects many intermediate encodings enc next . Given a correct enc (see line 2), each intermediate encoding enc next derived by a swap (see lines [7][8][9][10][11][12] is always an encoding with no conflicting codes (i.e. code swap does not introduce encoding conflicts).…”
Section: Correctnessmentioning
confidence: 99%
“…We discuss achieved results and future research in Section 7. This study is an extended version of [11] and includes the following changes. We review the CPOG-based design methodology in Section 2.2 and summarise differences with other existing behavioural synthesis approaches in Section 3.1.…”
Section: Introductionmentioning
confidence: 99%